ω-3 and ω-6 Polyunsaturated Fatty Acids Regulate the Proliferation, Invasion and Angiogenesis of Gastric Cancer Through COX/PGE Signaling Pathway - Ma, Jiachi; Zhang, Chensong; Liang, Wanqing; Li, Lei; Du, Jun; Pan, Chengwu; Chen, Bangling; Chen, Yuzhong; Wang, Yuanpeng (Frontiers in Oncology, 2022)
Abstract Background To investigate the effect of polyunsaturated fatty acids ω-3 and ω-6 and their metabolites prostaglandin PGE2 and PGE3 on proliferation, invasion and angiogenesis of gastric cancer. Methods RT-PCR and ELISA were used to detect the expression of COX-1 and COX-2 in gastric cancer cell lines. The effect of ω-3, ω-6, PFG2 and PEG3 on the proliferation, invasion and neovascularization of gastric cancer cells were measured by cell proliferation, invasion and angiogenesis assay in vitro. COX-2 siRNA was transfected into gastric cancer cells, and the expression of COX-2 protein was detected by Western blot. COX-2 gene silencing influenced matastic potential of gastric cancer cells were detected by WST-1, transwell chamber and angiogenesis assay, respectively. Results COX-2 was only expressed in MKN74 and MKN45 cells. In gastric cancer cell lines with positive COX-2 expression, ω-6 and PEG2 could significantly enhance the proliferation, invasion and neovascularization of gastric cancer cells, and after transfection with COX-2 siRNA, the effects of ω-6 and PEG2 on enhancing the proliferation, invasion and angiogenesis of gastric cancer cells were significantly attenuated; ω-3 and PEG3 could inhibit the proliferation, invasion and neovascularization of gastric cancer cells. In gastric cancer cell lines with negative COX-2 expression, ω-6 and PEG2 had no significant effect on the proliferation, invasion and neovascularization of gastric cancer; ω-3 and PEG3 could significantly inhibit the proliferation, invasion and angiogenesis of gastric cancer. Conclusion ω-6 PUFAs reinforce the metastatic potential energy of gastric cancer cells via COX-2/PGE2; ω-3 PUFAs inhibit the metastatic potential energy of gastric cancer via COX-1/PGE3.